2009
DOI: 10.1038/nm.1911
|View full text |Cite|
|
Sign up to set email alerts
|

The cerebral cavernous malformation signaling pathway promotes vascular integrity via Rho GTPases

Abstract: SUMMARYCerebral cavernous malformation (CCM) is a common vascular dysplasia that affects both systemic and CNS blood vessels. Loss of function mutations in the CCM2 gene cause CCM. Here we show that targeted disruption of Ccm2 in mice results in failed lumen formation and early embryonic death through an endothelial cell autonomous mechanism. We demonstrate that CCM2 regulates endothelial cytoskeletal architecture, cell-cell interactions and lumen formation. Heterozygosity at Ccm2, a genotype equivalent to hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
484
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(502 citation statements)
references
References 40 publications
(48 reference statements)
16
484
1
1
Order By: Relevance
“…This hyperpermeability is associated with RhoA kinase (ROCK) activation, and can be rescued by ROCK inhibition. 3,6,7 We also showed hyperpermeability to Evans blue dye in vivo in the brain and lungs of Ccm1 haploinsufficient mice, also rescued by ROCK inhibition. 3 The ROCK activity has been linked to increased CCM lesion burden in mice, and ROCK inhibition is being tested as a potential therapy to prevent CCM lesion development.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…This hyperpermeability is associated with RhoA kinase (ROCK) activation, and can be rescued by ROCK inhibition. 3,6,7 We also showed hyperpermeability to Evans blue dye in vivo in the brain and lungs of Ccm1 haploinsufficient mice, also rescued by ROCK inhibition. 3 The ROCK activity has been linked to increased CCM lesion burden in mice, and ROCK inhibition is being tested as a potential therapy to prevent CCM lesion development.…”
Section: Introductionmentioning
confidence: 60%
“…3,8,10 Statin medication was shown to reverse dermal hyperpermeability associated with heterozygous Ccm in mice. 6 Until the present study, it has not been determined whether vascular permeability measurements in the human brain could reflect the differences postulated mechanistically. Also, it is unknown whether differences in brain or CCM lesion permeability are associated with various aspects of clinical disease activity.…”
Section: Cerebral Cavernous Malformation As Vascular Permeability Dismentioning
confidence: 83%
“…Because we found that CCM1 loss-of-function also caused a loss of appropriate DELTA-NOTCH signaling, one could assume that the sprouting process must be highly disorganized with many additional capillary branches (22). Three studies have recently reported that CCM2 is essential for cardiovascular development and maintaining vascular integrity (28)(29)(30). Thus, it appears that the CCM proteins, which are not related but can form a complex (9), together keep adult endothelial cells quiescent.…”
Section: Discussionmentioning
confidence: 99%
“…11). Recent studies have implicated defective Rho signaling as one of the consequences of depletion (or overexpression) of the CCM1, CCM2, and CCM3 proteins (12)(13)(14). Further links between CCM3 and its kinase partners and cytoskeletal dynamics via the Golgi were also uncovered.…”
Section: Pp2amentioning
confidence: 99%